The Improved Models of Internet Pricing Scheme of Multi Service Multi Link Networks with Various Capacity Links - Puspita, FM; Seman, K; Taib, BM (Springer, 2024)
Internet Service Providers (ISPs) nowadays deal with high demand to promote good quality information. However, the knowledge to develop new pricing scheme that serve both customers and supplier is known, but only a few pricing plans involve QoS networks. This study will seek new proposed pricing plans are offered with multi service multi link networks involved. The multi service multi link Networks scheme is solved as an optimization model by comparing two models in multi QoS networks. The results showed that by fixing the base price and varying the quality premium or varying the base price and quality and setting up the equal capacity link values, ISP achieved the goal to maximize the profit.